2020
DOI: 10.1038/s41598-020-74441-x
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty quantification based cloud parameterization sensitivity analysis in the NCAR community atmosphere model

Abstract: Using uncertainty quantification techniques, we carry out a sensitivity analysis of a large number (17) of parameters used in the NCAR CAM5 cloud parameterization schemes. The LLNL PSUADE software is used to identify the most sensitive parameters by performing sensitivity analysis. Using Morris One-At-a-Time (MOAT) method, we find that the simulations of global annual mean total precipitation, convective, large-scale precipitation, cloud fractions (total, low, mid, and high), shortwave cloud forcing, longwave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 96 publications
(195 reference statements)
2
12
0
Order By: Relevance
“…A decrease in PRECT (∼3.7 to 3.1 mm/day) in response to an increase in dcs is also noted (Figure 9), which indirectly alters (decreases) the stability of the atmosphere (CAPE; Figure 7) and thus the convective precipitation (PRECC; Figure 9), since changes occur in CMP but not in convection parameterizations. This phenomenon was also reported for different CMP parameters by Lin et al (2016) and Pathak et al (2020). In addition, the increase in ai caused more ice particles to fall, thereby decreasing CLDHGH (∼85 to 78%), LWCF (∼30 to 19 W/m 2 ) and SWCF (−35 to −29 W/m 2 ), and IWP (0.1 to 0.06 kg/m 2 ) (Mitchell et al, 2008), while causing an increase in LWP from 0.044 to 0.049 kg/m 2 (Figures 7, 8).…”
Section: Response Of Simulated Qoi To Sensitive Parameterssupporting
confidence: 81%
See 4 more Smart Citations
“…A decrease in PRECT (∼3.7 to 3.1 mm/day) in response to an increase in dcs is also noted (Figure 9), which indirectly alters (decreases) the stability of the atmosphere (CAPE; Figure 7) and thus the convective precipitation (PRECC; Figure 9), since changes occur in CMP but not in convection parameterizations. This phenomenon was also reported for different CMP parameters by Lin et al (2016) and Pathak et al (2020). In addition, the increase in ai caused more ice particles to fall, thereby decreasing CLDHGH (∼85 to 78%), LWCF (∼30 to 19 W/m 2 ) and SWCF (−35 to −29 W/m 2 ), and IWP (0.1 to 0.06 kg/m 2 ) (Mitchell et al, 2008), while causing an increase in LWP from 0.044 to 0.049 kg/m 2 (Figures 7, 8).…”
Section: Response Of Simulated Qoi To Sensitive Parameterssupporting
confidence: 81%
“…While, the second-and higher-order sensitivity of dcs, ai, rhmini, rhmaxi, and eii together contribute about 7 and 20% of the total variance in different QoIs. Some previous studies using the predecessor version of this model have also argued that dcs and ai are the most sensitive parameters for the simulation of total precipitation over the tropical region (He and Posselt, 2015;Qian et al, 2015;Zhang, 2015;Pathak et al, 2020). Other studies that employed different models have also suggested dcs and ai to be highly sensitive to cloud distribution (e.g., Bony and Dufresne, 2005;Sanderson et al, 2008;Golaz et al, 2011;Gettelman et al, 2012).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations